ETIKA DIGITAL DAN PERLINDUNGAN DATA PRIBADI: UPAYA MENCEGAH KEJAHATAN SIBER DI KALANGAN REMAJA BERDASARKAN PASAL 39 AYAT 1 UU NOMOR 27 TAHUN 2022: Penguatan Kesadaran Etika Digital Remaja dalam Perspektif Undang-Undang Nomor 27 Tahun 2022 - Ali Baihaqi, Irfan; Isa Asyrofuddin, Muhammad; Amirudin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The rapid development of digital technology has encouraged adolescents to be more active on social media, online platforms, and various internet-based applications. However, such increased online activity also brings a higher risk of cybercrime, including data theft, phishing, account hacking, and identity misuse. This community service program aims to improve adolescents’ understanding of digital ethics and personal data protection in accordance with Article 39 paragraph (1) of Law Number 27 of 2022 on Personal Data Protection. The methods applied include educational seminars, digital literacy training, cybercrime case studies, and account security simulations, conducted using a participatory approach among senior high school students. The results revealed a significant increase in participants’ awareness of personal data protection, the ability to recognize privacy violations, and responsible use of digital platforms. Participants were also able to understand the legal consequences of misusing others’ personal data. Therefore, this community service program contributes to early cybercrime prevention, enhances awareness of personal data protection, and strengthens ethical digital behavior. In conclusion, continuous education and regulation-based digital literacy programs are strategic efforts to reduce cybercrime risks among adolescents.